Transcriptome-Wide Identification of miRNAs and Their Targets During Riboflavin-Promoted Dormancy Release in Lilium ‘Siberia’ - Xiaoping Xu; Chenglong Yang; Yiping Zheng; Wenjie Guo; Zhongxiong Lai; Shaozhong Fang (Horticulturae)
Dormancy release is an important process for improving the quality of cut-flower lily production and promoting the factory production of lily bulbs. However, the regulatory mechanisms of microRNAs (miRNAs) and their target genes during the dormancy release of lily remain elusive. Anatomy, transcriptomic, molecular biology, and transient transformation techniques involving subcellular localization were applied in our study. There were significant results showing that 0.1 mM riboflavin promoted dormancy release and floral bud differentiation and influenced the flowering time of the Lilium ‘Siberia’. Moreover, some differentially expressed miRNAs and their targets (miR395-y: LoAPS1, miR529-z: LoSPL14, miR396-y: LoCFDP1, miR1863-z: LoFBA3, miR399-y: LoDIT1, and miR11525-z: Lopgm) were identified and predicted. Exogenous riboflavin may activate primary metabolic processes and promote dormancy release in Lilium ‘Siberia’ bulbs. Furthermore, riboflavin upregulated genes related to the riboflavin pathway, H3K4me3 methylation, dormancy control, and the flowering pathway and downregulated dormancy maintenance genes. Moreover, riboflavin promoted endogenous riboflavin and acetyl-CoA accumulation. LoPurple acid phosphatase17 (LoPAP17), a pivotal gene of the riboflavin metabolism pathway, was subsequently cloned. LoPAP17 was most closely related to the orthologous genes of Acorus calamus, Asparagus officinalis, and Musa acuminata. The LoPAP17 protein was subcellularly located in the nucleus. Our study revealed that miRNAs and their target genes might regulate the primary metabolic pathway, promote the accumulation of endogenous riboflavin and acetyl-CoA, and affect protein acetylation during the riboflavin-promoted release of dormancy and flower bud differentiation in the Lilium Oriental hybrid ‘Siberia’.